Atoms of fire - Beiley, Dick (Virginia : Landmark Media Inc.)
Shows how carbon's structure allows it to be the backbone for macro molecules and why starch and not cellulose is digestible by humans.
Episode 5 Polymers and plastics
Narrator: Adam Salur
Keywords: Polymers; Polymers -- Analysis; Plastics; Macromolecular substances